Професійна освіта і підготовка посадових осіб з безпеки життєдіяльності - Кобилянський, О. В. (НТУ "ХПІ", 2010)
Проанализированы особенности преподавания дисциплин цикла “Безопасность жизнедеятельности" по образовательно-профессиональной программе подготовки специалистов экономического направления в высших учебных заведениях. Рассматриваются практические аспекты изучения этих дисциплин студентами в процессе подготовки к профессиональной деятельности.

The features of teaching of disciplines of cycle are analyzed “Safety of vital functions” after educationally professional by the program of preparation of specialists of economic direction in higher educational establishments. The practical aspects of study of these disciplines are examined by students in the process of preparation to professional activity.
Тrade education and preparation of public servants is from safety of vital functions
Keywords: освітня сфера; конкурентоспроможність; підготовка менеджерів; системи викладання; вищі навчальні заклади; компетентність